Work-life Balance: A Study On Banking Employees - Kaur , Rajwinder (Gyan Management Journal, 2020)
In  today's  competitive  business scenario,  concept  of  balancing  work  and  life  becomes  extremely  essential because it affects workplace job satisfaction & employees commitment towards the company.  The present study is undertaken in Banking Sector to identify the extent of balance in life and work and  also to examine the impact of balanced work and life on employee. A survey was conducted after taking  the approval from top management. For the present study, 250 questionnaires are filled by the different  employees of different banks. The results of the study suggested that 41.20% of the employees feel  imbalance in their work-life aspect. The main reasons of imbalance in work-life are work load with  high job responsibility and stressful working hours with insufficient breaks in banking sector. The study  also provides recommendations to improve balance in work-life.
Keywords: Banking Sector; Imbalance; Job Satisfaction; Work Load; Work-Life balance